2019
DOI: 10.3390/sym11111388
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things Meets Vehicles: Sheltering In-Vehicle Network through Lightweight Machine Learning

Abstract: An internet of vehicles allows intelligent automobiles to interchange messages with other cars, traffic management departments, and data analysis companies about vehicle identification, accident detection, and danger warnings. The implementation of these features requires Internet of Things system support. Smart cars are generally equipped with many (hundreds or even thousands of) sensors and microcomputers so that drivers gain more information about travel. The connection between the in-vehicle network and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In order to prove the efficiency of the this model, they applied it to other recent popular public datasets in the scope of CAN bus traffic intrusion detection. Xiao et al [ 30 ] proposed a lightweight ML algorithm based on RNN for IDS on the CAN bus network. The experimental evaluation using appropriate hyper-parameters demonstrated that the proposed model had good performance metrics, compared to LSTM and GAN models.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In order to prove the efficiency of the this model, they applied it to other recent popular public datasets in the scope of CAN bus traffic intrusion detection. Xiao et al [ 30 ] proposed a lightweight ML algorithm based on RNN for IDS on the CAN bus network. The experimental evaluation using appropriate hyper-parameters demonstrated that the proposed model had good performance metrics, compared to LSTM and GAN models.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Wang et al proposed a distributed anomaly detection system based on the hierarchical time memory (HTM) algorithm [19], which effectively realized the real-time prediction of the original CAN traffic data at the bit level. e method in [8,18,19] causes the loss of some information and relationships in the CAN network by establishing a model for an independent CAN ID or ECU [20], and the model becomes more complicated. Kang and Kang proposed a deep neural network (DNN)-based intrusion detection method [21], which used an unsupervised deep belief network (DBN) to pretrain the initialization parameters and test it on the simulation data set generated by the OCTANE platform.…”
Section: Mobile Information Systemsmentioning
confidence: 99%
“…Even with low-cost embedded boards, the accuracy of the proposed method was not degraded and thus the proposed method can be a practical solution for large-scale pig farms. In fact, this analysis of cost effectiveness is closely related with the "on-device" AI issue (i.e., processing deep networks directly on embedded devices instead of cloud server platforms) [51][52][53][54][55]. For continuous monitoring of individual pigs with a cloud server, we should transmit the video stream of each pig room into the cloud server.…”
Section: Appl Sci 2020 10 X For Peer Review 16 Of 23mentioning
confidence: 99%
“…Since low-cost embedded boards have more limited computing power than typical PCs, fast and accurate detection of individual pigs for low-cost pig monitoring applications is very challenging. Because this research direction for a light-weight pig detector is a kind of "on-device" AI [51][52][53][54][55], it can also contribute to the on-device AI community.…”
Section: Introductionmentioning
confidence: 99%